The Neoclassical Growth of China - Jesús Fernández-Villaverde; Lee Ohanian; Wen Yao (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies China's four-fold increase in per capita GDP relative to the U.S. between 1995 and 2019. First, we argue that China's growth pattern is very similar to that of several other East Asia economies that initially grew very quickly. Second, we show that a minimalist Ramsey-Cass-Koopmans model with a parsimonious TFP catch-up process can account for China's growth path and the growth paths of other East Asia economies at a similar stage of development. The growth paths of other East Asia economies and the model predictions suggest that China's growth will substantially slow, so much so that we find the U.S. growth rate will likely be higher than China's by 2043. We also find that China's income per capita will level off at roughly 44% of the U.S. level around 2100.
Keywords: E10; E20; O40; 330; China; East Asia; economic growth; Ramsey-Cass-Koopmans model; TFP catch up